Microbiome variability in invasive coral (Tubastraea aurea) in response to diverse environmental stressors - Girija, Gowri Krishna; Tseng, Li-Chun; Chen, Yu-Ling; Meng, Pei-Jie; Hwang, Jiang-Shiou; Ho, Ying-Ning (Frontiers in Marine Science, 2023)
The Indo-Pacific native azooxanthellate Tubastraea (Scleractinia) has been identified as an invasive marine species with substantial environmental, economic, and social implications worldwide. Despite their exceptional invasive capacity, our understanding of the role of their symbiotic microbiota in host resilience, as well as their response to ambient environmental conditions, remains limited. In this study, we analyzed the symbiotic bacterial communities found in the tissue and mucus of Tubastraea aurea from different habitats along the northeastern coast of Taiwan. These habitats included two extreme sites (a hydrothermal vent [HV] and a copper mining [CM] site) and two normal environments (inlet of a nuclear power plant [NPP] and a habitat adjacent to a conservation zone [CZ]). We employed fulllength 16S rRNA sequencing ( 1.5 kilobases) to determine coral-associated microbiome responses to local environments. Results showed significant variations in bacterial communities between corals from extreme and normal habitats. Chemoheterotrophic Endozoicomonas bacteria dominated the tissue samples from the HV and CM sites, whereas phototrophic Synechococcus cyanobacteria dominated the NPP and CZ sites. Hydrographic parameters such as pH, salinity, biological oxygen demand, turbidity, and concentration of heavy metals (e.g., Cu and Fe) increased at the HV and CM sites compared with those at the NPP and CZ sites. This difference created more stressful conditions at the HV and CM sites. The microbial assemblages associated with T. aurea exhibited a prevalence of diverse symbiotic bacteria that could potentially contribute to the host's ability to adapt and survive in challenging ecological conditions. Therefore, these advantageous microorganisms, along with the host's physiological mechanisms of dispersion, range expansion, and invasiveness, may enhance the resilience and ability of T. aurea to thrive in extreme environments.